The Targums : A Critical Introduction - Flesher, Paul Virgil McCracken (Book collections on Project MUSE., 2011)
The value and significance of the targums-translations of the Hebrew Bible into Aramaic, the language of Palestinian Jews for centuries following the Babylonian Exile-lie in their approach to translation: within a typically literal rendering of a text, they incorporate extensive exegetical material, additions, and paraphrases. These alterations reveal important information about Second Temple Judaism, its interpretation of its bible, and its beliefs. This remarkable survey introduces critical knowledge and insights that have emerged over the past forty years, including t.